2020
DOI: 10.21037/tp.2020.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral palsy in children: a clinical overview

Abstract: Cerebral palsy (CP) is a disorder characterized by abnormal tone, posture and movement and clinically classified based on the predominant motor syndrome-spastic hemiplegia, spastic diplegia, spastic quadriplegia, and extrapyramidal or dyskinetic. The incidence of CP is 2-3 per 1,000 live births. Prematurity and low birthweight are important risk factors for CP; however, multiple other factors have been associated with an increased risk for CP, including maternal infections, and multiple gestation. In most case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
227
0
22

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(255 citation statements)
references
References 57 publications
6
227
0
22
Order By: Relevance
“…Fit. Sports, 9(4) (2020) 27-30 | 29 of movement in children with cerebral palsy [10]. Successful physical therapy may include passive gentle range of motion exercises and stretches across major joints whereby increased range-of-motion results.…”
Section: The Potential Impact Of Physical Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Fit. Sports, 9(4) (2020) 27-30 | 29 of movement in children with cerebral palsy [10]. Successful physical therapy may include passive gentle range of motion exercises and stretches across major joints whereby increased range-of-motion results.…”
Section: The Potential Impact Of Physical Therapymentioning
confidence: 99%
“…Successful physical therapy may include passive gentle range of motion exercises and stretches across major joints whereby increased range-of-motion results. In addition, muscle strength is achieved by performing regularly scheduled progressively increasing resistive exercises involving all major muscle groups; specific physiotherapy exercises are designed to improve balance, postural control, gait, and assist with mobility and transfers (for example from bed to wheelchair [10]).…”
Section: The Potential Impact Of Physical Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral palsy (CP) is a group of permanent movement disorders attributed to non-progressive disturbances occurring during fetal or infant brain development (1). The prevalence of CP for all live birth ranges from 2 to 3 per 1,000 live births (2). However, this prevalence varies for different regions or countries depending on income level, and a higher prevalence has also been reported in infancy compared to all live births (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…CP has been defined as a group of permanent disorders affecting movement and posture, causing limitations in activity due to nonprogressive disturbances that affects the developing fetal or immature infant brain; and it is a resultant of non-progressive injury to the developing brain. 1,2 Various studies conducted worldwide reported the prevalence of 1.5 to >4 per 1000 live births. 3,4 In India, prevalence of CP was estimated to be 2.95 per 1000 live births.…”
Section: Introductionmentioning
confidence: 99%